Effect of eHealth-delivered exercise programmes on balance in people aged 65 years and over living in the community: a systematic review and meta-analysis of randomised controlled trials. Issue 6 (10th June 2022) - Ambrens, Meghan; Alley, Stephanie; Oliveira, Juliana S; To, Quyen; Delbaere, Kim; Vandelanotte, Corneel; Tiedemann, Anne
Abstract : Introduction: Exercise that challenges balance is proven to prevent falls in community-dwelling older people, yet widespread implementation and uptake of effective programmes is low. This systematic review and meta-analysis synthesised the evidence and evaluated the effect of eHealth-delivered exercise programmes compared with control on balance in community-dwelling people aged ≥65 years. Methods: Nine databases including MEDLINE, CINAHL and Embase, were searched from inception to January 2022 to identify randomised controlled trials evaluating eHealth-delivered exercise programmes for community-dwelling people aged ≥65 years, published in English that included a balance outcome. Primary outcomes were static and dynamic balance. Secondary outcomes included fall risk and fear of falling. We calculated standardised mean differences (SMDs, Hedges' g) with 95% CIs from random effects meta-analyses. Results: We identified 14 eligible studies that included 1180 participants. Methodological quality ranged from 3 to 8 (mean, 5). The pooled effect indicated that eHealth-delivered exercise programmes have a medium significant effect on static balance (11 studies; SMD=0.62, 95% CI 0.27 to 0.72) with very low-quality evidence. There was small statistically significant effect on dynamic balance (14 studies; SMD=0.42, 95% CI 0.11 to 0.73) with very low-quality evidence, and fall risk (5 studies; SMD=0.32, 95% CI 0.00 to 0.64) with moderate-quality evidence. No significant effect of eHealth programmes on fear of falling was found (four studies; SMD=0.10, 95% CI −0.05 to 0.24; high-quality evidence). Conclusion: This review provides preliminary evidence that eHealth-delivered exercise programmes improved balance and reduced fall risk in people aged ≥65 years. There is still uncertainty regarding the effect of eHealth delivered exercise programmes on fear of falling. PROSPERO registration number: CRD42018115098.